PEMBELAJARAN TRANSFORMATIF KURIKULUM MERDEKA DI ERA DIGITAL - Legi, Hendrik; Riwu, Maleachi; Hermanugerah, Prima (Yayasan Perguruan Kampus, 2023)
In this research, the author followed a series of careful and comprehensive research methods to investigate the implementation of Transformative Learning in the Context of the Independent Curriculum in the Digital Era. The aim of this research is to evaluate the effectiveness of transformative learning in changing educational approaches, as well as identifying its impact on students, teachers and the education system more broadly. The author begins by conducting an in-depth literature review to understand the conceptual and theoretical basis of transformative learning and the Independent Curriculum. Next, the author will collect data through various observations and document analysis. The collected data will be analyzed both qualitatively to answer research questions. The results of the analysis will be interpreted to evaluate the impact and effectiveness of transformative learning. The author draws conclusions based on research findings and puts forward recommendations for improving the implementation of transformative learning and policy suggestions. The results of this research will be disseminated through publication in scientific journals and shared with stakeholders in education for better contributions in facing the ever-changing demands of the world of education.